Histoplasma com derrame pleural: relato de um caso - Almeida, Marcos C. de; Vianna, Lucy G.; Moraes, Mário A. P. (Revista do Instituto de Medicina Tropical de São Paulo, 1990)
Pleural effusions are rare events accompaning histoplasmosis, and in general they are associated with acute forms of the disease. It is described here a case of histoplasmoma associated with pleuritic pain and pleural effusion.